German Labour Experiences Since World War Two: A Suggested Interpretation - Schmidt, Ingo (Labour / Le Travail, 2009)
The article examines the social and political developments in Germany, with particular emphasis on the working class, from the downfall of the Nazi regime to 2007. Analyzes the similarities and differences between East and West Germany during the Cold War years and the rising discontent following reunification in 1989.
Keywords: COLD War; 1945-1989; Employees; GERMANY; Labor Unions; NAZIS; SOCIALISTS; SOVIET Union; United States; WORLD War; 1939-1945